Real World Evidence on Second-Line Palliative Chemotherapy in Advanced Pancreatic Cancer - Gränsmark, Emma; Bågenholm Bylin, Nellie; Blomstrand, Hakon; Fredrikson, Mats; Åvall-Lundqvist, Elisabeth; Elander, Nils O. (Frontiers in Oncology, 2020)
Background: The outcome and tolerability of palliative second line chemotherapy for advanced pancreatic cancer (APC) in real life patients are largely unknown. Prognostic parameters for risk stratification and treatment guidance are lacking. Materials and methods: A population based multicenter retrospective cohort study was conducted, covering all APC patients who received palliative second-line chemotherapy between 2011 and 2018 at any cancer center in the South East Region of Sweden. Primary outcome was overall survival after second-line therapy (OS2). Time to treatment failure after second-line therapy (TTF2), hematological toxicity, and unplanned hospitalizations were key secondary outcomes. A number of baseline potentially prognostic parameters were assessed. Results: A total of 509 patients received first-line palliative chemotherapy, and of these 167 (33%) received at least one dose of second-line therapy and formed the final study population. Median OS2 was 5.2 months (95% CI = 4.7-5.7) and median TTF2 was 1.9 months (1.5-2.2). OS2 and TTF2 were similar regardless regimen, including comparison of the two most common regimens (fluoropyrimidine monotherapy vs fluoropyrimidine/oxaliplatin doublet). Multivariate analysis revealed that normal plasma albumin (≥35) and serum CA-19-9 above median (>1550) were independent predictors for OS2 (HR=0.21, p<0.001 and HR=2.03, p=0.009) and TTF2 (HR=0.22, p<0.001 and HR=2.03, p=0.01), while ECOG performance status >1 was predictive for TTF2 (HR=2.05, p=0.032). Grade 3-4 hematological toxicity was registered in 17 patients (10%). 50 (30%) had at least one event of hospitalization. Conclusion: The real world outcome of second line palliative chemotherapy for refractory APC remains dismal. Baseline plasma albumin, serum CA-19-9, and performance status emerge as key prognostic factors, and should be further studied as tools for individualized treatment decisions.